The norms of realism and the case of non-traditional casting - Abell, CEJ (Michigan Publishing, 2023)
This paper concerns the conditions under which realism is an artistic merit in perceptual narratives, and its consequences for the practice of non-traditional casting. Perceptual narratives are narrative representations that perceptually represent at least some of their contents, and include works of film, television, theatre and opera. On certain construals of the conditions under which realism is an artistic merit in such works, non-traditional casting, however morally merited, is often artistically flawed. I defend an alternative view of the conditions under which realism is an artistic merit in perceptual narratives. I identify the two forms of realism at issue in debates about the artistic merits of non-traditional casting, and identify the artistic norms that determine the conditions under which each constitutes an artistic merit. I argue that, independently of the relation between moral merits and artistic merits, non-traditional casting violates these norms less often than is sometimes assumed. Moreover, in certain circumstances, non-traditional casting affects realism in artistically meritorious ways. I conclude by considering the implications of my view for the practice of whitewashing.